2008
DOI: 10.1038/ismej.2008.109
|View full text |Cite
|
Sign up to set email alerts
|

The biofilm life cycle and virulence of Pseudomonas aeruginosa are dependent on a filamentous prophage

Abstract: Mature Pseudomonas aeruginosa biofilms undergo specific developmental events. Using a bacteriophage mutant, generated by deletion of the entire filamentous Pf4 prophage, we show that the phage is essential for several stages of the biofilm life cycle and that it significantly contributes to the virulence of P. aeruginosa in vivo. Here, we show for the first time that biofilms of the Pf4 phage-deficient mutant did not develop hollow centres or undergo cell death, typical of the differentiation process of wild-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
366
1
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 316 publications
(410 citation statements)
references
References 47 publications
25
366
1
4
Order By: Relevance
“…Other studies have recently demonstrated a high level of bacteriophage release in biofilms (Resch et al, 2005;Rice et al, 2009). The resulting lysis of cells may provide nutrients and allow the persistence of neighbouring cells.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have recently demonstrated a high level of bacteriophage release in biofilms (Resch et al, 2005;Rice et al, 2009). The resulting lysis of cells may provide nutrients and allow the persistence of neighbouring cells.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteriophages are highly abundant in all environments and are thought to outnumber prokaryotes in nature by a factor of 10 (Rohwer and Edwards, 2002;Rice et al, 2009). As opposed to phages that predominantly lyse cells, temperent phages can integrate as prophage into host cell genomes in a way that may benefit both host and prophage (Weinbauer, 2004;Chen et al, 2005).…”
Section: Mutants Lacking the Prophages Are Defective In Biofilm Formamentioning
confidence: 99%
“…The beststudied example in this regard is the role of the filamentous phage Pf4 in P. aeruginosa biofilm formation. Mutants lacking the phage form smaller colonies during the first days of biofilm formation and a potential role of phage-mediated cell lysis in eDNA release has been discussed but has not directly been demonstrated (Allesen-Holm et al, 2006;Rice et al, 2009). At later stages of biofilm development, Pf4 is thought to convert into a superinfective lytic form that causes cell death and hollowing of the structures, and, by that, significantly contributes to seeding dispersal of the community (Webb et al, 2003;Rice et al, 2009).…”
Section: Mutants Lacking the Prophages Are Defective In Biofilm Formamentioning
confidence: 99%
See 2 more Smart Citations